Radiation-Induced Graft Polymerization of High Reactive Polyisobutylene on Lignosulfonate - Liu, Xiaoqiu; Lu, Jilong; Zhang, Weina; Zhu, Guoyi; Zhu, Jianwei (Asian Journal of Chemistry, 2011)
In this paper, the radiation-induced graft copolymerization between lignosulfonate and high reactive polyisobutylene (HRPIB) was studied. Radiation-induced graft copolymerization was carried out at room temperature without any additives and radiation doses are 30 mrad. It could change the physical and chemical properties of lignosulfonate and extend the application range of lignin. The reaction products should have potential applications in the field of adhesives, flocculants and rubber additives.